STUDI IMPLEMENTASI PENDIDIKAN KARAKTER PADA PEMBELAJARAN MATEMATIKA PADA KELAS CERDAS ISTIMEWA BAKAT ISTIMEWA (CIBI) SMP NEGERI 2 SURAKARTA - Munawaroh Munawaroh; Tri Atmojo Kusmayadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of research was to describe the implementation of character education to mathematics learning, the constraints the teacher faced and the solution the teachers took to the constraints with the implementation of character education in mathematics learning in the gifted and talented class of SMP Negeri 2 Surakarta. This study was a descriptive qualitative research; the subject of researcher was one mathematics teacher  and six students in the grade VII gifted and talented class. Techniques of validating data used were researcher persistence and time triangulation. Techniques of analyzing data used were (1) data reduction, (2) data display, and (3) conclusion drawing and verification. The results of research are as follows. 1) The process of character education implementation to learning was below. (a) The development of logical, critical, creative and innovative thinking character was conducted by means of assignment, directing the students to the correct answer and to make decision with debriefing. (b) The development of hard work character was conducted by means of group assignment. (c) The development of curiosity character was conducted by providing the example of material existing in real life. (d) The development of independency character was conducted by assigning the material reading to be discussed in the next meeting. (e) The development of self-confidence character was conducted by means of facilitating the students writing the result on the blackboard. 2) The constraints the teacher faced and the solutions the teacher took were as follows. (a) In the implementation of logical, critical, creative and innovative thinking character, the students monopolized actively the debriefing process so that the teacher should limit and provide other students the opportunity of asking question. (b) In the implementation of hard work character, not all students in the classroom had equal hard work ethos. The solutions taken were to play motivation video and to convince them about the ability they had, to display the students’ work, and to reward the students with the best performance. (c) In the implementation of curiosity character, the students who did not want to think too hard responded poorly to the stimulus given. In this case, the teacher could give reward in the form of mark (grade). (d) In the implementation of self-confidence character, the students with less self-confidence would select the easy assignment in presenting the group assignment, and they explained in very soft voice. The solutions taken were to give more mark to the students explaining group assignment, and to direct the students in the presentation. For teacher independency character, the teacher did not face a significant constraint.Keywords: Implementation, Character Education, Gifted and Talented Class.